HUBUNGAN MARAH DENGAN PERILAKU AGRESIF PADA REMAJA - RINI HAYATI; SYAIFUL INDRA (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2018)
This research is motivated by teenage emotional turmoil and adolescent problem is generally caused by social role conflict, aggressive behavior is a manifestation of anger. This study aims to: (1) describe anger, (2) describe aggressive behavior in adolescents, (3) examine how correlated anger and aggressive behavior in adolescents. This research uses quantitative method of correlational descriptive type. The population of the study were all students of MTsS Lab.IKIP Al Washliyah Medan which amounted to 409 people, a sample of 203 people, selected by proportional stratified random sampling technique. The instrument used the Likert scale model to measure anger correlation with aggressive behavior in adolescents. Data were analyzed with descriptive statistics, correlation. using Pearson Correlation. The research findings show that: (1) angry picture is in moderate category, (2) description of aggressive behavior is in medium category, (3) angry relationship with aggressive behavior in adolescent correlation of 0.229 and significance level 0,001. The implications of these research results can be used as input to create a program of guidance and counseling services that can control anger and self-control in behaving aggressively in students aged teenagers at MTs.S Lab IKIP Al Washliyah Medan.